2020
DOI: 10.1115/1.4048122
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Salt Hydrate Latent Heat Thermal Energy Storage System With Porous Aluminum Fabric and Salt Hydrate as Phase Change Material With Enhanced Stability and Supercooling

Abstract: Phase change materials (PCM), especially salt hydrates possess high volumetric energy storage capacity in their transition temperature range. These materials are used in applications where it is necessary to store thermal energy due to temporary load shift between demand and availability. Thus, possible applications are HVAC, recovery of waste heat, and defense thermal management. In spite of salt hydrates potential, the practical feasibility of latent heat storage with salt hydrates is limited due to low powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…11,12 Except for conventional TES systems that use sensible heat, 13 TES systems, based on the latent heat of phase change materials (PCMs), attract more attention as they have a greater thermal energy storage capability. 14,15 Nowadays, latent heat thermal storage (LHTES) systems have made great development due to their high thermal energy storage potential. 16 In LHTES systems, usually using PCMs as storage media because of their ability to release or absorb thermal energy during a reversible liquid/solid phase change.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Except for conventional TES systems that use sensible heat, 13 TES systems, based on the latent heat of phase change materials (PCMs), attract more attention as they have a greater thermal energy storage capability. 14,15 Nowadays, latent heat thermal storage (LHTES) systems have made great development due to their high thermal energy storage potential. 16 In LHTES systems, usually using PCMs as storage media because of their ability to release or absorb thermal energy during a reversible liquid/solid phase change.…”
Section: Introductionmentioning
confidence: 99%
“…For a TES application requiring repeated thermocycling (i.e., repeated consecutive cycles of melting and freezing), CFT was demonstrated to be effective in reducing the degree of supercooling in LNT (from ~10 o C) to less than 1 o C (e.g., in the range of 0.5-1 o C). The authors demonstrated that using the CFT technique the LNT samples survived thermocycling tests that exceeded 800 cycles of repeated incomplete melting and complete solidification [25].…”
Section: Supercooling In Pcmsmentioning
confidence: 99%
“…During intermittent operation of electronic devices -a heat sink filled with PCM can limit the peak value of the local temperature transients by rapid melting (faster discharging cycle) and release the heat when the device is idle (slow period of freezing, i.e., slower charging cycle). During thermocycling of PCM, the power rating is typically higher during the charging cycle (i.e., during melting, since it is dominated by free-convection heat transfer) and the power rating is lower during the discharging cycle (i.e., during freezing, since it is dominated by conduction heat transfer and convection is almost negligible) [25]. Thus, this strategy helps with extending the time required to reach the peak temperature of the heat sink, especially under critical load conditions [29].…”
Section: Artificial Neural Network Principlesmentioning
confidence: 99%
“…For a TES application requiring repeated thermocycling (i.e., repeated consecutive cycles of melting and freezing), CFT was demonstrated to be effective in reducing the degree of supercooling in LNT (from ~10 • C) to less than 1 • C (e.g., in the range of 0.5-1 • C). The authors demonstrated that using the CFT technique the LNT samples survived thermocycling tests that exceeded 800 cycles of repeated incomplete melting and complete solidification [25].…”
Section: Supercooling In Pcmsmentioning
confidence: 99%